2013
DOI: 10.1186/1471-2458-13-472
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the adequacy of smoking cessation support for pregnant and postpartum women

Abstract: BackgroundSmoking in pregnancy exemplifies the relationship between tobacco use and health inequalities. While difficulty reaching and engaging this population in cessation support is often highlighted in the literature, there is limited research that explores the factors that shape the provision and use of support by this subpopulation. Using Ontario, Canada, as a case study, this study examines how the use of cessation support by women is encouraged or discouraged by cessation policy, programming and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 31 publications
2
66
0
3
Order By: Relevance
“…Pregnant and postpartum women who were current or former smokers had received inconsistent information; they were unsure whether smoking cessation during pregnancy was safe or stressful to the fetus and whether pregnant women were eligible for nicotine replacement therapy 64 . HCPs and women being investigated by CPS reported inconsistent policies and limited supportive services available to assist a mother in retaining custody of her child; several women had their children apprehended by CPS despite completing parenting programmes at the request of CPS 59,65 .…”
Section: Impact Of Policies On Maternal Healthcarementioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant and postpartum women who were current or former smokers had received inconsistent information; they were unsure whether smoking cessation during pregnancy was safe or stressful to the fetus and whether pregnant women were eligible for nicotine replacement therapy 64 . HCPs and women being investigated by CPS reported inconsistent policies and limited supportive services available to assist a mother in retaining custody of her child; several women had their children apprehended by CPS despite completing parenting programmes at the request of CPS 59,65 .…”
Section: Impact Of Policies On Maternal Healthcarementioning
confidence: 99%
“…"I think it is very limited…sort of a patchwork of strategies that are loosely weaved together." Key informant discussing the uncoordinated nature of smoking cessation resource 64 .…”
Section: Impact Of Policies On Maternal Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous research has suggested that the type of team a midwife works in (community/integrated vs. hospital/clinic) is far more important in determining smoking cessation referral behaviour than the cessation training received or length of time they have worked as a midwife (Beenstock et al ., 2012). A further perceived barrier to addressing prenatal smoking is lacking a cohesive and coordinated interorganizational strategy and the funding to implement it (Borland, Babayan, Irfan, & Schwartz, 2013). A lack of service protocols to implement cessation interventions has also been highlighted as an inhibiter of support access (Colomar et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption in pregnancy, besides the fact that threatens maternal health, affects the embryo growth and development [5], with possible damage on organogenesis. Brain and central nervous system damage, the occurrence of congenital malformations in the fetus, can also be consequences of exposure to the toxic action of alcohol during intrauterine life.…”
Section: Introductionmentioning
confidence: 99%